Preparing Foundation Financial Statements Based on ISAK 35 Based on Microsoft Access at Madani Sinergi Foundation, Sidoarjo - M. Khoirul Hasbi Asiddiqi; Shulthoni, Moch; Roziq, Ahmad (Journal of Islamic Economics Perspectives, 2023)
A non-profit organization is an organization that operates without the aim of making a profit. Non-profit organizations are growing very rapidly, one of which is a foundation. Foundations are institutions that receive finance from resource providers who do not expect rewards and other economic benefits. Therefore, there is a need for transparency of funds to convince funders and all parties in terms of the use of these funds. Currently, ISAK 35 is a guideline for the process of preparing non-profit oriented financial statements. This study aims to compile financial statements of foundations that are guided by ISAK 35 and based on Microsoft Access. The data obtained by researchers based on the results of interviews, observations, and documentation. Preparation of financial reports using Microsoft Access starts from making tables, relations between tables, queries, forms, and reports. The results of this study are expected to make it easier for non-profit organizations to prepare financial statements based on ISAK 35 based on Microsoft Access.